Paleodiversity of the Superfamily Ursoidea (Carnivora, Mammalia) in the Spanish Neogene, related to environmental changes - Abella, J.; Montoya, P.; Morales, J. (Journal of Iberian Geology, 2014)
In the present study we analyse the diversity of the Superfamily Ursoidea during the Neogene of the Iberian Peninsula to further compare it with that of the Neogene of Western Europe to find the different associations of this group. The results indicate that both the diversity and the taxonomy amongst these two regions show important variations, thus letting their interpretation in terms of climatic differentiation. We might relate variations in the abundance of the Ursoidea to the environmental fluctuations taking place during the Miocene and Pliocene. Therefore, they could enable us to reach the assessment of these biogeographical distributions in order to deduce the preferential niches of each different group of Ursoidea.